Acute and Subchronic Oral Toxicity Evaluation of Herbal Formulation: Piper crocatum Ruiz and Pav., Typhonium flagelliforme (Lodd.) Blume, and Phyllanthus niruri L. in Sprague–Dawley Rats - Retno Murwanti; A. Nurrochmad; Andayana P. Gani; Ediati Sasmito; Angela E. Edwina; Mayang K. Chandra; F. H. Suryawan; A. R. Wardana; null Natalia; Jelita L. S. R. Budiningsih (Journal of Toxicology)
Background. The product combination of Piper crocatum Ruiz. and Pav., Phyllanthus niruri Linn., and Typhonium flagelliforme (Lodd.) BL ethanolic extract (SKM) exerts immunomodulatory activity. However, the toxicity profile of the combination has never been investigated. Objective. This study aimed to establish the acute toxicity profile of the SKM product on Sprague–Dawley (SD) rats and its subchronic toxicity profile on female SD rats. Method. The acute and subchronic toxicity tests were conducted in accordance with OECD 423 and OECD 408, respectively. Result. The SKM product was safe up to 5000 mg/kg b.w. in male and female SD rats. In repeated doses of SKM for 90 days, the administration of 22.5, 45, and 90 mg/kg b.w. per day of the SKM product to female SD rats did not affect clinical signs, body weight, food and water consumption, hematological parameters, clinical chemical parameters, urinalysis, relative organ weights, and gross pathological and histopathological features compared with the control group. Conclusion. Analyses of these results suggest that the long-term oral administration of the SKM product for 90 days does not cause subchronic toxicity.